Impact of content features of digital micro-dramas on active aging: the serial mediation effect of emotional engagement and social connectedness - Li, Wei; Cheng, Shijing; Ling, Shuai; Zheng, Can (Frontiers in Psychology, 2025)
Due to the rapid development of digital media, micro-dramas have emerged as an important channel for cultural consumption and social participation among the elderly due to their concise narrative, emotional intensity, and convenient interactivity. This study leverages the theory of active aging to explore the impact mechanisms of the content characteristics of digital micro-drama (narrativity, emotional resonance, and interactivity) on active aging among the elderly, introducing emotional engagement and social connectedness as mediating variables. The study employs a questionnaire survey and structural equation modeling method to conduct an empirical analysis on a sample of 705 elderly individuals from urban China. The results indicate that the narrativity, emotional resonance, and interactivity of digital micro-dramas positively influence the level of active aging; emotional engagement demonstrates partial mediation in this process; and social connectedness plays a mediating role in several pathways. Furthermore, emotional engagement and social connectedness may exert a chain mediation effect, further strengthening the potential impact of micro-dramas on active aging. This study reveals the role of digital micro-dramas, as an emerging cultural form, in promoting psychological health and social participation among the elderly, providing theoretical support and practical insights for advancing the active aging strategy and digital cultural services for the elderly.